If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 20 = 9(x + -4) Reorder the terms: 20 + X = 9(x + -4) Reorder the terms: 20 + X = 9(-4 + x) 20 + X = (-4 * 9 + x * 9) 20 + X = (-36 + 9x) Solving 20 + X = -36 + 9x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + X = -36 + -20 + 9x Combine like terms: 20 + -20 = 0 0 + X = -36 + -20 + 9x X = -36 + -20 + 9x Combine like terms: -36 + -20 = -56 X = -56 + 9x Simplifying X = -56 + 9x
| (12-4i)(3+i)=0 | | c(ad)+x=bd+ad(yz) | | 5x^2=9x-5 | | 360-2x=100 | | 22n=100 | | -10y-3=7y | | (2abc)(-3abc)(-5a)= | | Y=30x+.10 | | -6v+2=1 | | xsquared-7x=-3 | | -6v+2=11 | | 49=2y+17 | | 5(2-4)=30 | | (2abc)(-3abc)(-5)= | | 2x(x+3)-3(2x-3)= | | x^3+-10x+25=0 | | (4v+1)(3+v)=0 | | x^3-10x+26=0 | | 2(x+1)=4x+2 | | 2y-24x=10 | | -2x^2-2x-12=0 | | -2=3y+7 | | -2x-9y=1 | | 36y=1 | | 28+24p=36p | | 2x^3-6x^2-x=0 | | a^3b^2(3a^2b)= | | 6-(3x-6)=7x-9 | | log(7)1= | | Log(x+12)-log(x)=1 | | 9-(2-3)-[3-(5-2)]-[2+(4-3)]= | | 46=3x+2y |